Toward an E-learning adoption: Sustainable technology used - Susanti, Leni; Alamsyah, Doni Purnama; Othman, Norfaridatul Akmaliah (2023)
The phenomenon that occurs in universities today is the increase in the use of e-learning during the Covid-19 pandemic. However, the readiness of students and universities is seen as too short. The purpose of this research is to examine the relationship between expected benefits, e-learning curriculum, and educational partners in supporting student e-learning adoption. This study supports the sustainability of technology used in e-learning concepts. This research method is a quantitative survey of students in the city of Bandung (Indonesia) who implement e-learning as a learning medium. Data from students were taken through a questionnaire and processed using SmartPLS. The analysis was carried out using regression analysis with research hypothesis testing. The results of the study found that the expected benefits, e-learning curriculum, and educational partners have a positive relationship with the e-learning adoption of students in online learning. The E-learning curriculum is an antecedent variable that has better support for e-learning adoption. The research findings explain that e-learning adoption in universities can be built by three aspects starting from the e-learning curriculum, expected benefits, to educational partners. There is important information from this research that can be used as information support on the implementation and sustainability of online learning. E-learning organizers are expected to be able to improve the concept of e-learning, especially in the curriculum, because it has an important role to increase student e-learning adoption.